Parents' Knowledge Attitude and Practice (KAP) about Retinopathy of Prematurity in Rural setting of Bangladesh: Doi: 10.36351/pjo.v36i2.992 - Das, Bimal Chandra; Ullah, ASM Wali; Alam, Muhammad Zahangir (Pakistan Journal of Ophthalmology, 2020)
Purpose: To measure the Knowledge, Attitude and Practices parents/caregivers about ROP in the rural setting of Bangladesh. Study Design: Cross-sectional descriptive study. Place and Duration of Study: Rural area of Bangladesh, from August 2019 to September 2019. Material and Methods: A total of 80 preterm babies’ parents/caregivers were interviewed. Quantitative data and qualitative data were also collected through 6 Informal Group Discussions and 2 In-depth Interviews. There was a one-day session with all persons involved with the study for clear understanding of the study goal and every item of the format and interview schedule. The study format and interview schedule were given to one social scientist and one public health expert in determining content validity. Their comments were incorporated in finalizing the research instruments. The filled-in formats and interview schedules were edited immediately after the collection. Both quantitative and qualitative data were collected for the study. Results: The most common risk factor for ROP was oxygen supply (79%), Bio-safety (67%) and weight (66%). The major reasons for not screening for ROP were lack of awareness (84%), lack of knowledge (48%), family related issues (77%), socio-economic condition (78%), distance (55%), frustration (65%) and overconfidence (52%). About 86.4% (CI: 80.3 – 85.2) had faced difficulties to obtain ROP services. We found significant association between facing treatment difficulties/guardian knowledge about ROP and time of age of screening for ROP (p <.001). Conclusion: The majority of parents/caregivers suggested for ROP screening, and put recommendations to improve mother anti-natal care (ANC) and strongly supported community awareness campaign to reduce the ROP related burden at rural setting.